Cervical stump carcinoma - Morales, Julio (2015)
The authors review the literature related to cervical cancer stump. Then they expose their personal experience that consists of 6 cases observed in the Clinical Gynecologic Clinical Hospital from 1937 to 1955 on a total of 8,000 hospitalized ill. Stump cancer was presented in 1.14% in relation to cervical cancer including a matching case. Admitting only true, this incidence is 0.95%. Regarding employment of total or subtotal hysterectomy, but prefer the former believe that subtotal can not be abandoned in the treatment of conditions requiring a hysterectomy. They insist on the need to carefully study the cervix before setting the operating behavior and control the remaining stump after subtotal hysterectomy.